Rejuvenation - Bridges, Kendall Vaughn (Kansas State University, 2022)
My desire with the lesson plans I describe in this report is to demonstrate a return to the beginnings of my career as a music teacher. The lessons, therefore, will show my return to grounding my choir students in a solid foundation of singing technique, understanding their voices, and mastering concepts such as breath management and resonance. I will show a return to good techniques that include structure and purpose. I will show a renewed understanding of my role as the voice teacher in the choir class. I will work to stay true to my philosophy that all students can learn if they desire, and I believe the videos will show that my students are learning to be wonderful singers with the hope that they will continue in my program and help shape it into the program that I know they deserve! My time with the professors in all my classes has been eye-opening and informative. I was reminded in Survey of Vocal Music for Adolescent Singers that I in fact, am a voice teacher, a role I have never placed on myself. It was the work and discussion in this class that helped my realize that I have the skill and the knowledge to help young singers develop healthy singing habits, I just needed to be reminded of my education. This has helped me a great deal in working with my changing voices. I am much more careful to listen to the individual voices as the sing be certain the are using their best skills to sing. History and Philosophy of Music Education saw to it that I reviewed my first philosophy, written in the early 90’s, and made sure that I was being true to what I thought so many years ago. I was pleased that many of my beliefs as an early educator had not changed, and I was equally proud that time and experience have encouraged some new thoughts in my philosophy. Advanced Choral Rehearsal Techniques had the most influence. Although my rehearsals have been successful, it was a nice reminder of the importance of routine when developing a choir program. For years, I have admittedly been more focused on product rather than process simply due to the make-up of my singers. I teach in a Title 1 school, as I have my entire career, and have become accustomed to teaching the song but never the mechanics in order to keep class moving and students working. I spend a great deal of time behind the piano, and while I am always proud of their performance, I fully know that taking the time to teach my students to read and understand music with conviction would have so more impact on their lives as singers. It was the introduction of new ideas and the discussions in this class that helped me gain a new focus on the importance of what, why, and how I rehearse on a daily basis.
Keywords: Return to basics; Rejuvenation; Teaching; Chorus